Diagnostic Approach and Successful Treatment of Ocular Tuberculosis - Siti Chadijah; Ovi Sofia; Herwindo Putranto (Majalah Oftalmologi Indonesia, 2021)
Introduction: The prevalence of ocular tuberculosis (TB) are 1% in patients with pulmonary TB and 20% in patients with extrapulmonary TB. The definitive diagnosis and its management are still challenging. This case highlights the diagnostic approach and successful management of ocular tuberculosis Purpose: To report the diagnostic approach and successful management of ocular tuberculosis.Case Presentation: A-15-Years-old-Girl, presented to outpatient clinic due to blurred vision on both eyes since 6 month ago. She was suffered from fever and solitaire mass along the neck lymph node 2 weeks before. The best corrected visual acuity (BCVA) of the right eye was 0.2 and the left eye 0.3. The ophthalmology examination of both eyes revealed mutton fat, 2+ flare, and 1+ cell, posterior synechia, koeppe and bussaca nodule, 4+ vitreous cells. Funduscopy were unremarkable due to vitritis. There was an elevation of erythrocyte sedimentation rate, positive mantoux test and Quantiferon-TB Gold. Chest radiograph showed fibrosis of the right lung. Fine needle aspiration biopsy of neck mass showed fibrotic tissue. Patient was diagnosed with tuberculous granulomatous panuveitis. She received anti-tuberculous therapy (ATT) along with high dose methylprednisolone 0.5 mg/BW/days on tapered dose. At 3 weeks follow up, vitritis was subsided and we revealed snowball, snowbanking, and optic disc swelling of both eyes that showed improvement at 11 weeks follow up. The BCVA become 1.0 at week-17 of therapy and remains stable until 8 months follow up. Conclusion: Diagnosis of ocular tuberculosis diagnose was made based on symptoms and signs of granulomatous panuveitis and supporting evidence of pulmonary TB ancillary tests. Significant clinical improvement was achieved after administration of ATT along with high dose oral steroid.